Distinct Characteristics of Early Summer Rainfall Over the Red River Delta and Southern Floodplain - Tuan, Bui Minh; Thi Hai Yen, Pham; Thi Mai, Ta; Huu Chinh, Ta; Thanh Hoa, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2025)
In this study, distinct characteristics of early summer rainfall over the Red River Delta and Southern Vietnam were investigated based on observed rainfall data, ERA5 reanalyzed data, and outgoing longwave radiation data. Statistical methods, including power spectrum analysis and linear regression, were applied. The results show a significant increase in rainfall in both regions from May 10 to May 16, which then remains at a high level. The results indicate a marked increase in rainfall in both regions between May 10 and May 16, after which rainfall remains consistently high. The increase is more pronounced in the Red River Delta, and the number of heavy rain days is also higher in this region compared to Southern Vietnam. On a seasonal time scale, the southwest monsoon is the main factor enhancing rainfall in both areas; however, moisture convergence caused by the monsoon is more enhanced in the Red River Delta. On intraseasonal time scale, rainfall in both regions exhibits strong oscillations in the period of 10-25 days, and these oscillations are associated with the activities of synoptic-scale low-pressure systems over the East Sea. The contribution of rainfall caused by intraseasonal processes tends to be higher during the first half of May in Southern Vietnam, whereas this value tends to be higher in mid-July in the Red River Delta.